2020
DOI: 10.1371/journal.pone.0234643
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared photoimmunotherapy is effective treatment for colorectal cancer in orthotopic nude-mouse models

Abstract: Background Photoimmunotherapy (PIT) employs the use of a near-infrared (NIR) laser to activate an antibody conjugated to a NIR-activatable dye to induce cancer cell death. PIT has shown to be effective in a number of studies, however, there are no data on its use in colorectal cancer in an orthotopic model. Methods Humanized anti-CEA antibody (M5A) was conjugated to NIR-activatable IRDye700DX (M5A-700). PIT was validated in vitro with a colon cancer cell-line, using a laser intensity of either 4 J/cm 2 , 8 J/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
(28 reference statements)
0
7
0
Order By: Relevance
“… 146 If the Nb is linked to anti-CEA Nb, it can dissolve CEA + tumor cells through NK cells in vitro models of human cells and tissues, and also suppress cancer cell growth in CEA + tumor transplanted mice, which fosters new thinking on the development of anti-tumor Nb. 147 …”
Section: Nanobody-modified Car-t Therapymentioning
confidence: 99%
See 1 more Smart Citation
“… 146 If the Nb is linked to anti-CEA Nb, it can dissolve CEA + tumor cells through NK cells in vitro models of human cells and tissues, and also suppress cancer cell growth in CEA + tumor transplanted mice, which fosters new thinking on the development of anti-tumor Nb. 147 …”
Section: Nanobody-modified Car-t Therapymentioning
confidence: 99%
“…146 If the Nb is linked to anti-CEA Nb, it can dissolve CEA + tumor cells through NK cells in vitro models of human cells and tissues, and also suppress cancer cell growth in CEA + tumor transplanted mice, which fosters new thinking on the development of anti-tumor Nb. 147 There was too much of a correlation between immune infiltration and tumor microenvironment (TME), which has turned out to be enormously successful in clinical cancer immunotherapeutic. 148,149 CAR-T cell therapy is one of the research hotspots of tumor immunotherapy and has a good prospect for the treatment of hematological tumors, which makes patients' own T cells genetically modified to better attack cancer cells (Figure 6B).…”
Section: Nanobody-modified Car-t Therapymentioning
confidence: 99%
“…Elekonawo et al used a CEA-expressing human CRC cell line, LoVo, subcutaneously implanted in 18 mice demonstrating labetuzumab-IR700 plus PIT significantly slowed tumor growth compared to PIT alone or labetuzumab-IR700 alone [34]. Hollandsworth et al demonstrated similar findings in an LS174T orthotopic murine model [35].…”
Section: Orthotopic and Intraperitoneal Mouse Modelsmentioning
confidence: 93%
“…Beyond co-clinical trials, transplant mouse models are also considered useful tools for studying immunotherapy. Hollandsworth et al 97 verified that near-infrared photoimmunotherapy is an effective method for the treatment of CRC using humanized mice. To overcome the limitations of antibody therapy for immune checkpoint blockade, Lee et al 98 explored a novel blockade in traditional oriental medicine, called Sanguisorbae Radix extract (SRE).…”
Section: Drug Testingmentioning
confidence: 99%